Law and Policy for the Quantum Age - Jay Hoofnagle, Chris (Social Sciences, 2021)
Law and Policy for the Quantum Age is for readers interested in the political and business strategies underlying quantum sensing, computing, and communication. This work explains how these quantum technologies work, future national defense and legal landscapes for nations interested in strategic advantage, and paths to profit for companies.